A randomized clinical trial in adults and newborns in South Africa to compare the safety and immunogenicity of bacille Calmette-Guérin (BCG) vaccine administration via a disposable-syringe jet injector to conventional technique with needle and syringe. Issue 37 (8th September 2015) - Geldenhuys, Hennie D.; Mearns, Helen; Foster, Jennifer; Saxon, Eugene; Kagina, Benjamin; Saganic, Laura; Jarrahian, Courtney; Tameris, Michele D.; Dintwe, One B.; Van Rooyen, Michele; Luabeya, Kany-Kany A.; Hussey, Gregory; et al.
Abstract Introduction Intradermal bacille Calmette-Guérin (BCG) vaccination by needle-free, disposable-syringe jet injectors (DSJI) is an alternative to the Mantoux method using needle and syringe (NS). We compared the safety and immunogenicity of BCG administration via the DSJI and NS techniques in adults and newborn infants at the South African Tuberculosis Vaccine Initiative (SATVI) research site in South Africa. Method Thirty adults and 66 newborn infants were randomized 1:1 to receive intradermal BCG vaccine (0.1 mL in adults; 0.05 mL in infants) via DSJI or NS. Wheal diameter (mm) and skin fluid deposition at the site of injection (SOI) were measured immediately post-vaccination. Adverse events and SOI reactogenicity data were collected 30 min and 1, 2, 4, and 12 weeks after vaccination for adults and at 30 min and 4, 10, and 14 weeks for infants. Blood was collected in infants at 10 and 14 weeks to assess BCG-specific T-cell immune responses. Results More infant BCG vaccinations by DSJI deposited >5 μL fluid on the skin surface, compared to NS (49% versus 9%, p = 0.001). However, all 12 infant vaccinations that did not produce any SOI wheal occurred in the NS group (36%, p < 0.001). Median wheal diameter, in participants for which an SOI wheal formed, did not differ significantly between groups in infants (combined 3.0 mm IQR 2.0 to 4.0, p = 0.59) or in adults (combined 9.0 mm IQR 7.0 to 10.0, p = 0.13). Adverse events were similar between study arms. Proportion of participants with BCG scars after three months did not differ in adults (combined 97%, p = 0.67) or infants (combined 62%, p = 0.13). Frequencies of BCG-specific clusters of differentiation 4 (CD4) and clusters of differentiation 8 (CD8) T-cells co-expressing IFN-γ, TNF-α, IL-2, and/or IL-17 were not different in the DSJI and NS groups. Conclusion BCG vaccination of newborn infants via DSJI was more likely to deliver an appropriate intradermal wheal at the SOI as compared to NS, despite leaving more fluid on the surface of the skin. Safety, reactogenicity, and antigen-specific T-cell immune responses did not differ between DSJI and NS techniques.